The duplicity of the signs: Immanence and transitivity: immanence et transitivité (Signifiances (Signifying), 2019)
The saussurian critic of a direct relationship between language and world imply the double essence of language. A sign is both a sound and content and is given in the system of language (immanence) as well as in speech or discourse. The immanence separates language from the world in a way that constitutes the possibility of talking about the world. This is the transitivity in the sense of Benveniste : to speak is to speak of something (“parler-de”). The dublicity of the sign signifies then that it is both a difference (“diabolique”) and a relationship (“symbolique”) to the world.